SAFETY OF REINFORCED CONCRETE BRIDGES WITH SPANS STRUCTURES - Y. V. Krasnoshchekov (Вестник СибАДИ)
Introduction. The author presents the results of the reliability analysis of the structural systems in spans of bridges.Materials and methods. The analysis of published materials for the purpose of using them in the design of reinforced concrete bridges, in connection with changes in design standards and tightening of regulatory requirements for safety is made by the author.Results. The results of surveys of slab superstructures indicate the reliability and durability of typical structures operated under normal conditions, but in emergency situations there is a danger of progressive collapse. Therefore, in such conditions, split schemes of multi-span structures are unacceptable. The research tasks to ensure the durability of slab superstructures are formulated. In particular, the task of developing the method of durability calculation in case of one of the pillars failure in the continuous span structure, taking into account the dynamic effect is illustrated.Discussion and conclusion. Changes in design of slab structures of bridge cause the necessity to study the reliability and failure in emergency situations.